2011
DOI: 10.1203/pdr.0b013e318220c08a
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Amniotic Fluid Pattern for Prenatal Diagnosis of Esophageal Atresia

Abstract: Prenatal diagnosis of esophageal atresia (EA) may improve the outcome of affected neonates by allowing optimization of both prenatal and postnatal care. Prenatal sonographic detection is based on polyhydramnios and/or nonvisualization of the fetal stomach bubble, two signs with a large number of etiologies. We evaluated a biochemical approach to improving diagnostic efficiency. We compared amniotic fluid biochemical markers in 44 EA cases with 88 polyhydramnios and 88 nonpolyhydramnios controls. Both matched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 29 publications
0
44
0
2
Order By: Relevance
“…Biochemical analysis of amniotic fluid was available only in one case. It did not show low alpha-fetoprotein and/or low proteins level as seen in Bartter syndrome [7], however, the compression of the stomach by the large multicystic kidney in that case may have modified the biochemical markers, leading to a suspicion of esophageal atresia [8]. That compression of the digestive tract may also have played a role in the development of the polyhydramnios in that case.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Biochemical analysis of amniotic fluid was available only in one case. It did not show low alpha-fetoprotein and/or low proteins level as seen in Bartter syndrome [7], however, the compression of the stomach by the large multicystic kidney in that case may have modified the biochemical markers, leading to a suspicion of esophageal atresia [8]. That compression of the digestive tract may also have played a role in the development of the polyhydramnios in that case.…”
Section: Discussionmentioning
confidence: 67%
“…In one case (#4), therapeutic amnioreduction (removing 2 l of amniotic fluid) was performed at 32 weeks of gestation. Biochemical analysis of amniotic fluid was performed, but, surprisingly, showed a high gammaglutamyl transpeptidase, alpha-fetoprotein, and total protein levels as described in esophageal atresia [8]. The BBartterindex^ [7] was 8 (normal > 1.2).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study (12), we demonstrated that the association of ultrasound scan screening and AF biochemistry showed 98% sensitivity and 100% specificity in EA diagnosis. However, no comprehensible and plausible pathophysiological explanation was provided for the specific biochemical AF-EA pattern we observed associating high GGTP and normal AMP activities.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the suspicion of EA is usually based on these findings at ultrasound with, however, a high false-positive rate and a poor detection rate of ~50% (3,(8)(9)(10)(11). In a previous study based on a series of 44 cases of EA, we observed that amniotic fluid (AF) biochemistry had potential additional value in prenatal diagnosis, with a significant difference for total protein, α-fetoprotein, and γ-glutamyl transpeptidase (GGTP) between the EA group (whatever the anatomical type) and the control group (12). These markers are part of AF biochemical patterns used for prenatal diagnosis of different gastrointestinal diseases as previously described (13,14).…”
mentioning
confidence: 97%